2022
DOI: 10.3389/fcvm.2022.919224
|View full text |Cite
|
Sign up to set email alerts
|

Explainable machine learning models for predicting 30-day readmission in pediatric pulmonary hypertension: A multicenter, retrospective study

Abstract: BackgroundShort-term readmission for pediatric pulmonary hypertension (PH) is associated with a substantial social and personal burden. However, tools to predict individualized readmission risk are lacking. This study aimed to develop machine learning models to predict 30-day unplanned readmission in children with PH.MethodsThis study collected data on pediatric inpatients with PH from the Chongqing Medical University Medical Data Platform from January 2012 to January 2019. Key clinical variables were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Osteoporosis is a type of common bone disorder defined by WHO, characterized by low BMD and the deterioration of bone micro-architecture, leading to raised bone fragility and subsequent increased fracture risks [ 2 ]. Clinicians care more about conditions after osteoporotic fractures have occurred; however, it is more important to prevent and detect osteoporosis before fractures happen, in order to avoid unnecessary readmissions, additional healthcare costs, and an increased burden on medical systems, society, and individuals [ 4 , 31 ]. Osteoporosis is common among postmenopausal women, and pain, frailty or fall-associated fractures usually cause readmission, which can be avoided effectively by adequate pharmacotherapy and favorable management [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a type of common bone disorder defined by WHO, characterized by low BMD and the deterioration of bone micro-architecture, leading to raised bone fragility and subsequent increased fracture risks [ 2 ]. Clinicians care more about conditions after osteoporotic fractures have occurred; however, it is more important to prevent and detect osteoporosis before fractures happen, in order to avoid unnecessary readmissions, additional healthcare costs, and an increased burden on medical systems, society, and individuals [ 4 , 31 ]. Osteoporosis is common among postmenopausal women, and pain, frailty or fall-associated fractures usually cause readmission, which can be avoided effectively by adequate pharmacotherapy and favorable management [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that machine learning-based models have better performance than prediction models using traditional logistic regression. In 2022, Duan MJ et al developed a CatBoost model based on machine learning to predict the risk of 30-day unplanned readmission in pediatric pulmonary hypertension patients, with an AUC of 0.81 Compared to the traditional logistic regression algorithm, the machine learning model showed significantly better performance, with an AUC of 0.72 [ 27 ]. In 2021, Ke Wang et al developed a machine learning-based XGBoost risk stratification tool to accurately assess and stratify the 3-year risk of all-cause mortality in patients with heart failure due to coronary heart disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, the claim of interpretability is warranted, for instance in manuscripts that use methods such as logistic regression or even more-advanced methods such as explainable-boosting machines [70,71]. However, a large volume of studies (a small sampling for example [72][73][74][75][76]) are in-actuality putting forward blackboxes as explainable by using SHAP or similar methodologies.…”
Section: Critical Look At the Applied Literaturementioning
confidence: 99%